Strategic HRM and SME innovation: a chain mechanism of learning-resilience pathway and nonlinear environmental dynamism - Wang, Jiabao; Zhang, Jiaxue; Zhao, Yi (Frontiers in Psychology, 2025)
In an increasingly competitive business environment, organizational innovation has become crucial for enterprises seeking to establish and maintain a competitive advantage. This study aims to investigate how SHRM drives innovation in SMEs through the chain mediation of organizational learning and resilience, while exploring the nonlinear moderating role of environmental dynamism. Grounded in dynamic capability theory, we propose a three-dimensional framework that integrates internal organizational mechanisms with external environmental contingencies. Utilizing a three-wave survey design with 256 technology-focused SMEs in China’s Yangtze River Delta region, we employed hierarchical regression analysis and bootstrap mediation tests to validate hypothesized relationships. The findings indicate that SHRM significantly contributes to promoting organizational innovation in SMEs. Organizational learning (as a knowledge-building process) and resilience (as an adaptive capacity) sequentially mediate this relationship, forming an internal “learning-resilience” mechanism in which knowledge acquisition fosters robust adaptation, thereby synergistically enhancing innovation capability development. Furthermore, environmental dynamism exhibits a significant inverted U-shaped moderating effect: moderate levels amplify SHRM’s innovation-enhancing effects, whereas excessive dynamism diminishes its efficacy, revealing a “dynamic-changing” boundary condition. Theoretically, this study advances dynamic capability theory by unraveling the synergistic interplay between internal capability-building processes and external environmental contingencies. Practically, this study provides actionable insights for SME managers to strategically allocate human resources, cultivate learning-resilience capacities, and adaptively respond to environmental turbulence, thereby fostering sustainable innovation in volatile markets.